Conceptualizing Integration of Islamic Education and Education in General at UIN Syarif Hidayatullah Jakarta - Sururin Sururin; Mundzir Suparta; Didin Nuruddin Hidayat; Syahirul Alim; Dhuha Hadiyansyah; Arif Zamhari (UIN Sunan Ampel Surabaya, 2021)
UIN Jakarta, with its distinct characteristics, focuses on integrating Islamic and general education as a unity. This research focuses on the oldest faculty: The Faculty of Educational Sciences (FITK, hereafter). This study aims to a) explore the concept of integration of Islamic and general education at FITK, and b) find out the extent to which lecturers at FITK understand the concept of integration. The approach used in this research was phenomenology. It employed the qualitative method to describe the concept of integration of Islamic and general education and reveal the extent of lecturers' understanding of scientific integration. The results showed that at the conceptual level, the paradigm of reintegration of Islamic and general education is an integration of Islamic knowledge and values, which is two-way: from secular sciences to Islamic values and from conventional Islamic religious materials to secular sciences. The study also found that scientific integration has long been present in the FITK academic environment. However, the concept of scientific integration itself does not appear to be a uniformity which causes many different interpretations from each study program, even from lecturers in the FITK environment. In addition, the concept of scientific integration has not been fully understood by each leader in the academic community of UIN Jakarta, mainly due to the lack of socialization and no appointment for specific institutions responsible for managing this integration process.